Pendampingan Industri Kecil Pengecoran Logam Ceper Untuk Meningkatkan Kemandirian Pasokan Peralatan Tambang - Towip Towip; Yuyun Estriyanto; Herman Saputro; Taufik Wisnu Saputra (DEDIKASI: Community Service Reports, 2022)
Developing substitution products for mining equipment parts in local industries will have a significant economic impact. In addition, it will create independence in the supply of mining components, not relying on imports. However, Ceper metal casting area is still using traditional methods. This community service aims to improve product design and skills to support the supply chain availability of consumable mining equipment parts. Designing from existing components is not easy for small industries; therefore, it needs assistance from university experts. The method used design assistance in the production of bucket-adapter consumable parts. The mechanical engineering study program team assists with three stages of the process: (1) scanning, (2) triangulation, and (3) CAD modeling. The results showed that consumable parts had been successfully submitted to an industry partner to proceed to the following stages: (4) CAM and (5) machining. The consumable parts design improves quality and independence in manufacturing mining equipment parts. The local industry appreciated this activity because a good design can improve the process of developing consumable mining equipment parts.